In vitro cytotoxic potential of Swietenia macrophylla King seeds against human carcinoma cell lines - Goh, B.H.; Kadir, A.H. (Academic Journals, 2011)
Fruits of Swietenia macrophylla King (sky fruit) have been widely used in traditional medicine to treat various diseases including hypertension and diarrhea. The cytotoxic activity of the crude ethanol extract of the seeds of S. macrophylla and its fractions was assessed against selected human cancer cell lines, namely, HCT 116 (colon carcinoma), KB (nasopharyngeal epidermoid carcinoma), Ca Ski(cervical carcinoma) and MCF-7 (breast carcinoma) by using MTT assay. The S. macrophylla ethyl acetate fraction (SMEAF) showed the most potent activity against HCT116 cell line (IC50 = 35.35 μg/ml ± 0.50 ug/ml) in a dose- and time-dependent manner and was further investigated for its possible mechanisms using flow cytometric analysis. Annexin V and PI binding of treated HCT116 cells indicated apoptosis induction by SMEAF in a dose-dependent manner. The induction of apoptosis was further confirmed both by DNA fragmentation using TUNEL assay and the externalization of phosphatidylserine using Annexin V/PI stain. The cell cycle analysis revealed a prominent increase in sub-G1 population at concentrations of 0.05 mg/ml and above. Results also showed that SMEAF induced collapse of the mitochondrial membrane potential after 24 h and caused depletion in total intracellular glutathione. The result of the present investigation is the first report on the potential anticancer activity of S. macrophylla seeds and its possible mechanisms of action on cancer cell proliferation.